Golgin Imh1 and GARP complex cooperate to restore the impaired SNARE recycling transport induced by ER stress - Wang, Yi-Hsun; Chiu, Wan-Yun; Chen, Yan-Ting; Cai, Pei-Juan; Wu, Yu-Chieh; Wu, Jia-Lu; Chen, Bo-Han; Liu, Ya-Wen; Yu, Chia-Jung; Lee, Fang-Jen S. (Cell reports (Cambridge), 2022)
The accumulation of misfolded proteins in the endoplasmic reticulum (ER) induces the unfolded protein response (UPR), which acts through various mechanisms to reduce ER stress. While the UPR has been well studied for its effects on the ER, its impact on the Golgi is less understood. The Golgi complex receives transport vesicles from the endosome through two types of tethering factors: long coiled-coil golgin and the multisubunit Golgi-associated retrograde protein (GARP) complex. Here, we report that ER stress increases the phosphorylation of golgin Imh1 to maintain the GARP-mediated recycling of the SNAREs Snc1 and Tlg1. We also identify a specific function of the Golgi affected by ER stress and elucidate a homeostatic response to restore this function, which involves both an Ire1-dependent and a MAP kinase Slt2/ERK2-dependent mechanism. Furthermore, our findings advance a general understanding of how two different types of tethers act cooperatively to mediate a transport pathway. [Display omitted] •Tunicamycin (TM)-induced ER stress partially impairs GARP function on the Golgi•Imh1 is necessary for GARP-mediated Snc1/Tlg1 recycling under TM-induced stress•TM induces Slt2/ERK2-dependent Imh1 phosphorylation to maintain Snc1/Tlg1 recycling•Defects in N-linked glycosylation govern post-ER stress response at the late Golgi Wang et al. present the cooperative action of two different classes of tethers, golgin Imh1 and GARP complex, in mediating proper recycling of SNAREs Snc1/Tlg1 under ER stress. They show that ER stress induces an Ire1-independent response mechanism, which involves the MAP kinase Slt2/ERK2-dependent Imh1 phosphorylation to maintain Snc1/Tlg1 transport.